PERANAN KOMUNIKASI ANTARPRIBADI DOSEN DENGAN MAHASISWA DALAM MENINGKATKAN MINAT BELAJAR MAHASISWA POLITEKNIK UNGGUL MEDAN - Syahrani Devi; Suwardi Lubis; Zulkifli Zulkifli (JURNAL PROINTEGRITA, 2019)
able to give understanding, feeling happy and motivation to the students in studying. Interpersonal communication is a very big effect communication, in this case, it is able to influence other people. It is caused of both sides who are doing communication meet each other and face to face without having media to give their message, there is no space between communicator and communicant in communicating.The purpose of the research is knowing the role of lecturer's interpersonal communication to the students in increasing students' interest. Be expected that the students are able to concentrate in following their class and playing gadget no morein the class.The method of research is used descriptive by qualitative approach. Technic of collecting data is taken by doing observation and interviewing to the respondents and informants.The result of research shows that lecturer's interpersonal communication has important role to increase the students' interest in studying. Lecturer's interpersonal communication which has openness, empathy, supportiveness, positiveness and equality dimensions are